Isoflavone supplementation in postmenopausal women does not affect leukocyte LDL receptor and scavenger receptor CD36 expression: A double‐blind, randomized, placebo‐controlled trial. Issue 9 (21st April 2016) - Engelbert, Ann Katrin; Soukup, Sebastian T.; Roth, Alexander; Hoffmann, Nadine; Graf, Daniela; Watzl, Bernhard; Kulling, Sabine E.; Bub, Achim
Abstract : Isoflavones may reduce cardiovascular disease risk through effects on lipoprotein metabolism. In a randomized, double‐blind, placebo‐controlled trial in parallel design, we investigated effects of a soy isoflavone extract on leukocyte LDLR and CD36 receptor expression, serum lipoprotein concentrations, and body composition parameters in 170 healthy postmenopausal women. Despite a moderate increase in serum LDL, isoflavone intervention had no effect on leukocyte LDLR and CD36 expression. Abstract : Scope: Isoflavones are discussed to improve serum lipoproteins and body composition and to reduce cardiovascular disease risk in postmenopausal women (PMW). LDL receptors (LDLR) and scavenger receptor CD36 (CD36) play a pivotal role in the regulation of plasma LDL‐cholesterol concentrations (LDL‐chol). We investigated the impact of isoflavones on the receptor expression of both receptors in leukocytes of PMW. Methods and results: A randomized, double‐blind, placebo‐controlled trial in parallel design was conducted to assess the effects of an isoflavone‐enriched soy extract (117.4 mg/day isoflavone aglycone equivalents) for 12 weeks on serum LDL‐chol, LDLR, and CD36 expression on leukocytes in 170 healthy PMW. Baseline and after 12 weeks, blood lipid concentrations, anthropometric data and body composition were determined. Receptor expression on leukocytes was measured by means of flow cytometry. After the intervention, no significant differences were found for LDLR and CD36 expression on leukocytes. A significant increase of serum LDL‐chol was shown for the isoflavone group ( p = 0.03) after 12 weeks. Body fat content and VAT were not affected. Conclusion: Isoflavone supplementation for 12 weeks did not change LDLR and CD36 expression on leukocytes of PMW and did not affect body fat content and visceral adipose tissue (VAT), but slightly increased serum LDL‐chol.